Stiffness methods for compaction control: the geogauge device - Conde, M. C. (2010)
Soil compaction is a critical point in the construction of highways, airports embankment and foundations. The current specifications address embankment compaction in terms of density and water content. However, achieving a certain physical properties does not guarantee acceptable performance. So, a comprehensive experimental testing program is under development, on compacted layers to investigate the feasibility of developing a stiffness-based specification for embankment soil compaction quality control. In this paper the correlation between the geogauge device output and in situ density and water content measured in dam under construction are presented and discussed.